Management Of Grade II Tooth Mobility Associated With Chronic Periodontitis Using A Fiber-Reinforced Composite Resin Extracoronal Splint: A Case Report - Azzah Putri Farohyani; Edi Karyadi; Aprilia Yuanita Anwaristi (CV. AFDIFAL MAJU BERKAH, 2026)
Chronic periodontitis is defined as an inflammatory condition of the periodontal tissues caused by specific subgingival microorganisms, resulting in the progressive destruction of the periodontal ligament and supporting tissues of the teeth. The primary clinical characteristic of chronic periodontitis is detectable clinical attachment loss, often accompanied by periodontal pocket formation and changes in the density and height of the alveolar bone. This condition may lead to pathological tooth migration, resulting in diastema formation and increased tooth mobility, which can ultimately cause tooth loss. Increased tooth mobility may negatively affect masticatory function, aesthetics, and patient comfort. One of the treatment modalities used to stabilize mobile teeth is splinting. Splinting combined with occlusal adjustment is intended to reduce and control the progression of tooth mobility. Case Report: A 54-year-old female patient presented to Soelastri Dental Hospital with a chief complaint of mobility of the lower anterior teeth that had been present for approximately six months. The patient reported that the teeth felt loose during mastication, particularly when contacting the maxillary teeth. Intraoral examination revealed Grade 2 tooth mobility in teeth 32, 31, 41, and 42. Bleeding on probing was observed in the mandibular anterior region. Periodontal pocket depths around teeth 32, 31, 41, and 42 ranged from 5 to 6 mm. Radiographic examination demonstrated alveolar bone loss associated with these teeth. Management of this case involved the placement of a fiber-reinforced composite splint extending from teeth 33 to 43. Fiber splinting was selected because of its advantages, including high mechanical strength, excellent adhesive properties, biocompatibility, satisfactory esthetics, and ease of clinical application. Evaluation one week after splint placement showed favorable outcomes, with no signs of gingival inflammation or food impaction in the splinted area, as well as satisfactory occlusal relationships.